STUDI TENTANG IMPULSE BUYING PADA KONSUMEN RANCH MARKET BUKIT DARMO BOULEVARD SURABAYA - Herawati, Wiwik (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2017)
Impulse buying (unplanned purchases) becomes one of the most preferred focal points by many market participants. In one study of impulse buying, it shows that 30-50% of all modern market purchases (supermarkets) have been classified by the buyers themselves as impulse buying (unplanned purchases). Therefore, market participants compete to find out more about how the process, the factors that influence it and the impact of unplanned purchases (Foroughi, et al., 2011). Ranch Market Bukit Darmo Boulevard Surabaya has used several ways to encourage customers to make unplanned purchases (impulse buying). The existence of massive discounts on the product, making consumers interested to buy one or more than one product. Consumers can take advantage of credit card or debit card payments when customers do not have the cash to pay for product spending and this will support unplanned purchases. There are several individual factors that influence consumer impulse buying that is Shopping enjoyment, Impulse buying Tendency, Hedonic Shopping Value, and Emotional Positive. This study aims to find out Impulse buying on the consumers of Pasar Hill Market Darmo Boulevard Surabaya.